Determination of Fipronil and Its Metabolites in Tea by Gas Chromatography-Negative Ion Chemical Ionization-Mass Spectrometry - MA Yiying, HAO Yu, ZHANG Peng, LIU Mengmeng, YU Yang, SUN Xinyao, YU Litao (Shipin Kexue, 2023)
In this paper, a gas chromatography-negative ion chemical ionization-mass spectrometry (GC-NICI-MS) method was established for the determination of fipronil and its metabolites fipronil sulfone and fipronil sulfoxide in tea. Fipronil and its metabolites were extracted from samples with acetonitrile, purified by liquid-liquid partition with n-hexane followed by chromatography on a PSA-SPE column, detected by GC-NICI-MS, and quantified by external standard method. The results showed that chromatographic separation was achieved within 16 min. The linear range for the four analytes was 0.002–0.200 μg/mL, with correlation coefficient (R2) larger than 0.999. The detection limit (RSN = 10) was 0.002 mg/kg, and the relative standard deviation (RSD) was less than 5%. At spiked concentration levels of 0.002, 0.010 and 0.020 mg/kg, the recoveries ranged from 96.33% to 102.50%. The developed method has a wide linear range, high accuracy and good repeatability, and allows the rapid and accurate detection of trace amounts of fipronil and its metabolites in commercially available tea.